A Comparison of Fentanyl and Flurbiprofen Axetil on Serum VEGF‐C, TNF‐α, and IL‐1ß Concentrations in Women Undergoing Surgery for Breast Cancer. Issue 6 (8th May 2014) - Wen, Yiyun; Wang, Mingde; Yang, Jinfeng; Wang, Yichun; Sun, Huiping; Zhao, Jianghong; Liu, Weizhen; Zhou, Zhengyu; Deng, Hongwu; Castillo‐Pedraza, Catalina; Zhang, Yi; Candiotti, Keith A.
Abstract Background Vascular endothelial growth factor‐C (VEGF‐C), tumor necrosis factor‐α (TNF‐α), and interleukin‐1ß(IL‐1ß) have been shown to be associated with the recurrence and metastasis of breast cancer after surgery. This study tested the hypothesis that patients undergoing surgery for breast cancer, who received postoperative analgesia with flurbiprofen axetil combined with small doses of fentanyl (FA), exhibited reduced levels of VEGF‐C, TNF‐α, and IL‐1ß compared with those patients receiving fentanyl alone (F). Method Forty‐women with primary breast cancer undergoing a modified radical mastectomy were randomized to receive postoperative analgesia with flurbiprofen axetil combined with fentanyl or fentanyl alone. Venous blood was sampled before anesthesia, at the end of surgery, and at 48 hours after surgery, and the serum was analyzed. The primary endpoint was changes in the VEGF‐C concentrations in serum. Results Group FA patients reported similar analgesic effects as group F patients at 2, 24, and 48 hours. At 48 hours, mean postoperative concentrations of VEGF‐C in group F patients were higher than in group FA patients, 730.9 versus. 354.1 pg/mL (P = 0.003), respectively. The mean postoperative concentrations of TNF‐α in group F patients were also higher compared with group FA patients 27.1 vs. 15.8 pg/mL (P = 0.005). Finally, the mean postoperative concentrations of IL‐1ß in group F were also significantly higher than in group FA 497.5 vs. 197.7 pg/mL (P = 0.001). Conclusion In patients undergoing a mastectomy, postoperative analgesia with flurbiprofen axetil, combined with fentanyl, were associated with decreases in serum concentrations of VEGF‐C, TNF‐α, and IL‐1ß compared with patients receiving doses of only fentanyl.